Bistachybotrysins A–C, three phenylspirodrimane dimers with cytotoxicity from Stachybotrys chartarum. Issue 3 (1st February 2018) - Zhao, Jinlian; Feng, Jiamin; Tan, Zhen; Liu, Jimei; Zhang, Min; Chen, Ridao; Xie, Kebo; Chen, Dawei; Li, Yan; Chen, Xiaoguang; Dai, Jungui
Graphical abstract: Abstract: Bistachybotrysins A–C (1 –3 ), three phenylspirodrimane dimers representing an unusual [6, 6, 7, 6]-tetracyclic skeleton with a central 2, 10-dioxabicyclo[4.3.1]decan-7-ol core fused with two phenyl units, were isolated from a fungal strain, Stachybotrys chartarum CGMCC 3.5365. The structures of1 –3 were elucidated through extensive spectroscopic data analysis, including Mo2 (AcO)4 -induced and calculated electronic circular dichroism (ECD).1 and2 exhibited potent cytotoxicity against four human tumor cell lines with IC50 values in the range of 2.8–7.5 μM. Furthermore, a possible biogenesis for1 –3 is proposed.